2006
DOI: 10.2106/jbjs.e.00248
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bulb Syringe and Pulsed Lavage Irrigation with Use of a Bioluminescent Musculoskeletal Wound Model

Abstract: Pulsed lavage is a more effective and efficient method of irrigation to remove bacteria in a complex musculoskeletal wound. In the model we used, pulsed lavage irrigation with 3 L of saline solution resulted in a reduction of approximately the same amount of bacteria as did irrigation with 9 L with use of a bulb syringe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 25 publications
0
65
1
1
Order By: Relevance
“…PL also resulted in the same quantitative drop of bacteria numbers with 3 l of irrigant that was achieved in 9 l using the bulb system. The authors concluded that PL was a more effective and efficient method of irrigation to remove bacteria than a conventional irrigation technique [90].…”
Section: Infection In Conflict Wounded-future Directions In Research mentioning
confidence: 99%
“…PL also resulted in the same quantitative drop of bacteria numbers with 3 l of irrigant that was achieved in 9 l using the bulb system. The authors concluded that PL was a more effective and efficient method of irrigation to remove bacteria than a conventional irrigation technique [90].…”
Section: Infection In Conflict Wounded-future Directions In Research mentioning
confidence: 99%
“…At 1,4,8,12,24,36,48,72,96,120, and 144 h, pellets were removed, oven dried at 378C for 1 h, and weighed. The pellets were then reimmersed in fresh DI water.…”
Section: Dissolution Testingmentioning
confidence: 99%
“…3) in 20 ml phosphate buffered saline (PBS) in a 378C water bath. At 1,4,8,12,24,36,48,72,96,120,144,168, and 240 h, aliquots were removed and frozen at À408C. At each time point, the pellets were removed and placed in 20 ml fresh PBS.…”
Section: Elution Testingmentioning
confidence: 99%
See 2 more Smart Citations